Strategi Marketing Public Relation Traveloka Dalam Promosi Pemesanan Hotel Menggunakan Awkarin sebagai Key Opinion Leader: The Marketing Public Relation Strategy of Traveloka in Promoting Hotel Booking by Utilizing Awkarin as a Key Opinion Leader - Yunisa Rizki, Sendy; Amalina, Avinasiwi (Jurnal Media Penyiaran, 2023)
In contemporary times, the accessibility of news through social media and the proliferation of influential figures known as Key Opinion Leaders (KOLs) have rendered KOL services indispensable in realizing marketing public relations strategies. This article delves into the utilization of KOLs and social media platforms by Traveloka, a leading technology company in Southeast Asia, to enhance its marketing public relations endeavors. Through an examination of Traveloka's strategies, particularly its collaboration with the KOL Awkarin, this study sheds light on the framing and agenda-setting techniques employed to shape public perception and awareness. Furthermore, it explores the effectiveness of these strategies in influencing public opinion and driving engagement, particularly among the 18-30 age demographic. The findings underscore the significance of social media as a potent tool for reaching target markets and enhancing brand visibility. Through qualitative analysis and a constructivist paradigm, this study offers insights into the evolving landscape of marketing public relations in the digital age, highlighting the symbiotic relationship between companies, KOLs, and social media platforms in shaping consumer behavior and perceptions